Response to direct-acting antiviral agents in chronic hepatitis C patients with end-stage renal disease: a clinical experience - YILMAZ, YUSUF (ASSOC MEDICA BRASILEIRA, 2019)
OBJECTIVE: The recent development of direct-acting antiviral agents (DAAs) has dramatically changed the treatment of chronic hepatitis C, and interferon-based regimes have become a poor treatment choice in clinical practice. Today DAAs offer shorter, well-tolerated, highly effective curative therapies. This study aimed to evaluate the effectiveness and safety of DAAs in patients with end-stage renal disease and HCV genotype 1 infection in real clinical practice. METHODS: Thirty-six patients who attended our clinic, were diagnosed with chronic hepatitis C (CHC), undergoing hemodialysis, and fulfilled the criteria of age >18 years, genotype 1 infection, with a detectable HCV RNA level were considered for the study. Patients with GT1a infection received OBV/PTV/r plus DSV plus RBV for 12 weeks; GT1b infected patients received this regimen without RBV for 12 weeks. RESULTS: The study was conducted on 33 patients. The mean age was 52.30 +/- 13.77 years, and 70 % of them were male. By the fourth week of treatment, HCV RNA levels decreased below 15 IU/ml in all patients. Sustained virologic response (SVR) 12 rate was 100%. Nine patients had side effects during treatment. Of the patients with side effects, 89.9% were in group 1a and 11.1% in group lb. CONCLUSION: In this study, treatment with OBV/PTV/r and DSV with or without RBV resulted in high rates of sustained virologic response in HCV GT1-infected patients with end-stage renal disease (ESRD). SVR was achieved in all patients with few side effects.
Keywords: Hepatitis C; End-Stage Renal Disease; Sustained Virologic Response; SUSTAINED VIRAL RESPONSE; VIRUS GENOTYPES; INFECTION; INTERFERON; METAANALYSIS; EFFICACY; OMBITASVIR/PARITAPREVIR/RITONAVIR; COMBINATION; IMPAIRMENT; MANAGEMENT